Evaluation of Life Insurance Market Development in Poland During the Years 1991-2010 - Grzebieniak, Andrzej (Olsztyn Economic Journal, 2012)
Radical changes in Poland during the last decade of the 20th c. causednot only a significant acceleration of Poland’s economic growth rate but also rapid increase in the importance of insurance for the national economy. The penetration coefficient, i.e. the ratio of the gross premium written to the GDP, which in case of the total premiums increased from 1.83% in 1991 to 3.83% in 2010, and in case of life insurance from 0.26% to 2.31% respectively, is considered one of the synthetic measures of that importance. Although the Polish insurance market is developed far less than the European Union market where that coefficient is 7.9% and 4.8% respectively those differences decrease every year. The similar trend is presented by the depth coefficient that is the per capita insurance premium that additionally in case of life insurance increases faster than in case of the insurance sector as a whole. This indicates a relatively good life insurance market development rate in Poland although that market still ranks within the second half of the total number of the European Union countries’ domestic markets.